Culex (Diptera: Culicidae) Mosquitoes in Jazan Region, Saudi Arabia, and Their Molecular Identification - Noureldin, Elsiddig; Dafalla, Ommer; Hakami, Abdualziz; Jubran, Mohammed; Alzhrani, Ahmed; Mujally, Muhannad; Shajari, Othman; Khardali, Ali; Eisa, Zaki (International Journal of Zoology, 2021)
Morphological characteristics have been the gold standard method to identify mosquito species. However, morphological identification has many limitations including lack of expertise and damaging of external characters due to improper specimen handling. Therefore, we used the polymerase chain reaction technique (PCR) as an integrated tool to identify Culex mosquito species to establish a more precise and reliable identification system related to their spatial distribution in Jazan region. We identified Culex mosquito species and subspecies using taxonomic keys, and then we used the polymerase chain reaction technique (PCR) as an integrated tool to confirm and refine the list of Culex mosquito species in the region. Phylogenetic trees were constructed for the identified species, and their distinctive clustering was compared with their reference’s species in the GenBank. We identified 7026 adult Culex mosquitoes belonging to 4 species. Culex tritaeniorhynchus was the predominant species (45%), followed by Cx. quinquefasciatus (32%), then Culex sitiens (20%), and Cx. pipiens (3%). The most infested areas by Culex in the region were Gizan and Sabya. The PCR achieved 100% success in identifying the four Culex mosquito species. We also report the molecular identification of Cx. quinquefasciatus and Cx. pipiens species for the first time in Jazan region while the molecular identification of Cx. tritaeniorhynchus and Cx. sitiens was reported for the first time in Jazan region and the whole Saudi Arabia. This study utilized for the first time PCR to identify Culex mosquito species in Jazan region. The PCR is a complementary and integrated taxonomy-based identification tool for mosquito species. This integration has the capacity to promote and enhance vector surveillance and control programs, as well as defining the genetic diversity of species in the region.